Negative CO2 emissions via enhanced silicate weathering in coastal environments. (5th April 2017) - Meysman, Filip J. R.; Montserrat, Francesc
Abstract : Negative emission technologies (NETs) target the removal of carbon dioxide (CO2 ) from the atmosphere, and are being actively investigated as a strategy to limit global warming to within the 1.5–2°C targets of the 2015 UN climate agreement. Enhanced silicate weathering (ESW) proposes to exploit the natural process of mineral weathering for the removal of CO2 from the atmosphere. Here, we discuss the potential of applying ESW in coastal environments as a climate change mitigation option. By deliberately introducing fast-weathering silicate minerals onto coastal sediments, alkalinity is released into the overlying waters, thus creating a coastal CO2 sink. Compared with other NETs, coastal ESW has the advantage that it counteracts ocean acidification, does not interfere with terrestrial land use and can be directly integrated into existing coastal management programmes with existing (dredging) technology. Yet presently, the concept is still at an early stage, and so two major research challenges relate to the efficiency and environmental impact of ESW. Dedicated experiments are needed (i) to more precisely determine the weathering rate under in situ conditions within the seabed and (ii) to evaluate the ecosystem impacts—both positive and negative—from the released weathering products.